2007
DOI: 10.1620/tjem.212.81
|View full text |Cite
|
Sign up to set email alerts
|

Development of Glomerular Endothelial Cells, Podocytes and Mesangial Cells in the Human Fetus and Infant

Abstract: The process of glomerular development consists of four developmental stages: vesicle (V) stage, S-shaped body (S) stage, capillary loop (C) stage and maturation (M) stage. However, the development of glomerular endothelial, mesangial and epithelial cells in fetal and infant kidneys remains unclear. In order to determine the characteristics of human glomerular development, we investigated the process of glomerular development by staining fetal and infant kidneys for CD31, CD34 and FB21, markers for endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
3
16
0
1
Order By: Relevance
“…To discern the cellular expression of PMAT in the glomeruli, double immunofluorescence labeling was performed on human kidney cryosections using established cell type-specific markers for podocytes, mesangial cells, and glomerular endothelial cells-the three major cell types that make up the glomerulus. No overlap of specific PMAT staining was observed with ␣-smooth muscle actin (␣-SMA), a cell body marker for mesangial cells (13), or CD31, a cell surface marker for endothelial cells (24) (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…To discern the cellular expression of PMAT in the glomeruli, double immunofluorescence labeling was performed on human kidney cryosections using established cell type-specific markers for podocytes, mesangial cells, and glomerular endothelial cells-the three major cell types that make up the glomerulus. No overlap of specific PMAT staining was observed with ␣-smooth muscle actin (␣-SMA), a cell body marker for mesangial cells (13), or CD31, a cell surface marker for endothelial cells (24) (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…In the human fetal kidney, research has shown that the maturation of glomerular endothelial cells is ongoing until approximately 35–39 weeks gestation [35], which follows the completion of nephrogenesis at 32–36 weeks [26, 36]. Indeed, the term control lambs exhibited significantly greater capillary length than the gestational controls which is suggestive of increased growth in relation to increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Mesangial cells play an essential role in many aspects, for example, formation of capillary loops during development, contraction to regulate capillary flow, and removal of macromolecules [13], but the severe proliferation of MC causes functional damage of the kidneys.…”
Section: Introductionmentioning
confidence: 99%